Inspection of intraocular lens with dual-side view optical coherence tomography - Wu, Qian (2021)
Intraocular lens (IOL) is widely used for cataract treatment. Its optical properties are crucial to obtain a good treatment efficacy and thus need to be evaluated and controlled. In this study, we propose a novel method based on optical coherence tomography (OCT) for noncontact and accurate in vitro measurement of thickness, refractive index and dioptric power of IOL implants. The OCT setup is specially designed to create two sampling optics, called dual-side view OCT (DSV-OCT), which allows for imaging IOL from the two opposite sides simultaneously in single OCT volume scanning. This can produce a three-dimensional surface contour without suffering image distortions due to the refraction of the curved surface. Then, the thickness and surface curvature can be easily computed from the surface contours. In addition, DSV-OCT is able to measure the refractive index. Three IOLs with different dioptric powers (5D, 20D and 28D) were chosen to evaluate this method. The results show that this method is capable to provide a comprehensive and accurate evaluation of IOLs from the aspects of thickness, refractive index and dioptric power, and hence can be potentially used as a quality assurance tool by IOL manufacturers.